Eosinophilic gastroenteritis in a patient with Bruton's tyrosine kinase deficiency. Issue 5 (3rd February 2016) - Yamazaki, Susumu; Ohtsuka, Yoshikazu; Yokokura, Tomoaki; Yokota, Rena; Honjo, Asuka; Inage, Eisuke; Baba, Yosuke; Mori, Mari; Suzuki, Ryuyo; Iwata, Tsutomu; Shimizu, Toshiaki
Abstract: Eosinophilic gastrointestinal diseases (EGID) are relatively rare diseases characterized by eosinophilic infiltration of the gastrointestinal tract resulting in various gastrointestinal symptoms. EGID are often caused by allergic reactions or systemic eosinophilic disorders, but their comorbidity with Bruton's tyrosine kinase (BTK) deficiency has not been previously documented. Here, we report a case of eosinophilic gastroenteritis (EG) in a patient with BTK deficiency. Despite adequate replacement immunoglobulin (Ig) therapy, trough serum IgG was not maintained. To identify the underlying cause of the low trough level and chronic diarrhea, the intestine was investigated on endoscopy. We also screened for the variable number of tandem repeat polymorphism in FCGRT . Genetic analysis could not explain the low trough IgG, but endoscopy indicated eosinophilic enterocolitis. EG may be an important differential diagnosis when primary immunodeficiency patients have chronic diarrhea or continued low serum IgG.